A Comparative Analysis of Social Media Addiction Levels Between Male and Female Adolescents in Jayapura City - Asriati Asriati; Fransina Alfonsina Issac; Natalia Paskawati Adimuntja; Chrisin Debora Nabuasa (Universitas Mandala Waluya, 2025)
Social media users among teenagers have increased in Jayapura City since the COVID-19 pandemic. Excessive use of social media can lead to addiction, which can result in decreased sleep quality, psychological problems, increased non-communicable diseases, and other health problems. This study aims to examine the level of social media addiction among teenagers based on age and gender. This study uses a cross-sectional study design. The sample consisted of 297 respondents aged 15-19 years at SMA Negeri 2 Jayapura. The sampling technique used accidental sampling. The instrument used was the Internet Addiction Test (IAT) questionnaire. Statistical tests used Pearson Correlation and Independent t-tests. There was a significant relationship between age and the level of social media addiction (p-value=0.030), there was a difference in the level of social media addiction between males and females (p-value=0.002), and there was no difference in the level of addiction based on class (p-value =0.687). Age and gender are related to the level of social media addiction among adolescents in Jayapura City. There is a need to improve digital literacy with a gender-sensitive approach to reduce the impact of depression, anxiety, and body image disorders. In addition, strengthening regulations on social media use and increasing supervision and screen time restrictions from parents and school rules are necessary.